2018
DOI: 10.1002/jper.18-0146
|View full text |Cite
|
Sign up to set email alerts
|

Clinico‐radiographic evaluation of 1% alendronate gel as an adjunct and smart blood derivative platelet rich fibrin in grade II furcation defects

Abstract: PRF+ ALN treated defects exhibited better clinical and radiographic outcomes suggestive of enhanced periodontal regeneration when compared to PRF alone treated sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
22
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 33 publications
6
22
1
4
Order By: Relevance
“…Our study is the first RCT-based research that supports the superiority of PRF plus 1%ALN over PRF alone in periodontal bone regeneration. But we noticed that all RCTs reporting this combined strategy lacked an important control group which only received 1%ALN [10][11][12]. Although our meta-analysis showed PRF plus 1%ALN produced much better outcomes on periodontal bone regeneration than PRF alone, it's still necessary to know how much profit are acquired by using PRF plus 1%ALN in comparison to 1%ALN alone.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Our study is the first RCT-based research that supports the superiority of PRF plus 1%ALN over PRF alone in periodontal bone regeneration. But we noticed that all RCTs reporting this combined strategy lacked an important control group which only received 1%ALN [10][11][12]. Although our meta-analysis showed PRF plus 1%ALN produced much better outcomes on periodontal bone regeneration than PRF alone, it's still necessary to know how much profit are acquired by using PRF plus 1%ALN in comparison to 1%ALN alone.…”
Section: Discussionmentioning
confidence: 88%
“…Search Results. After selection according to our preestablished protocol, 14 RCTs were included for quantitative meta-analysis [10][11][12][23][24][25][26][27][28][29][30][31][32][33]. The details of search procedure were presented in study flowchart ( Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…11 To avoid these adverse effects, controlled clinical studies and animal studies have evaluated the efficiency of local/topical use of ALN gel adjunct to scaling and root planing in periodontitis treatment and demonstrated a new therapeutic possibility. [12][13][14][15][16][17] Recently, Wanikar et al 12 evaluated the effects of 1% ALN gel combined with platelet-rich fibrin in the treatment of class II furcation defects, evaluating bone defect volume through cone beam computed tomography, probing pocket depth, clinical attachment level, and horizontal probing depth. The results showed that the association of 1% ALN plus platelet-rich fibrin provided to obtain better results in periodontal treatment.…”
Section: Introductionmentioning
confidence: 99%